1980
DOI: 10.1093/geronj/35.6.827
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Adipose Mass and Cellularity Through the Adult Life of Rats Fed Ad Libitum or a Life-Prolonging Restricted Diet

Abstract: Male Fischer 344 rats were either fed ad libitum (Group A) or 60% of the ad libitum intake (Group R) starting at 6 weeks of age; the latter is a life prolonging food restriction. Total adipose mass increased with increasing age in both Group A and Group R rats until about 70% of the life span after which it declined. The results indicate that the lower adipose mass of the Group R rats is probably not related to life prolongation. Adipocyte hypertrophy is involved in growth of the epididymal and perirenal depot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
85
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(101 citation statements)
references
References 0 publications
11
85
1
Order By: Relevance
“…The increase of body fat percentage seems to occur even in animals fed an energy-restricted diet, if this diet contains energy sufficient for maintaining body weight (29). This fact also was recognized in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…The increase of body fat percentage seems to occur even in animals fed an energy-restricted diet, if this diet contains energy sufficient for maintaining body weight (29). This fact also was recognized in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Such a conclusion may not be correct, however, in view of the data from a previous study on body composition of AL and DR rats. Our earlier work (2) showed that, during the period of life prior to the beginning of terminal weight loss, the body fat content of the AL rats averaged 17% of body weight, a value that was much greater than the 11% body fat content found in the DR rats. In addition, body fat was markedly decreased during terminal weight loss before a reduction in lean body mass was observed (2,33).…”
Section: Discussionmentioning
confidence: 78%
“…Both food restriction and adiposity have been demonstrated to affect longevity in rodents. [43][44][45] All of the animals monitored for lifespan duration in our study were allowed to eat ad libitum, therefore, we suggest adiposity had a greater influence in longevity difference over that of food intake. Although our fat-pad analyses were performed at P60, the Adiposity reduction by Kv1.3 deletion K Tucker et al further acceleration and then plateau in body weight measured during the first 10 months of age, would suggest that the relative comparison in adiposity across the genotypes would persist throughout the lifespan of the animal.…”
Section: Discussionmentioning
confidence: 95%